Prevalence of untreated second canal in the mesiobuccal root of maxillary molars and its association with apical periodontitis: A cone beam computed tomography study (Research, Society and Development, 2021)
This study aimed to evaluate the prevalence of mesiobuccal 2(MB2) canals not located/treated in maxillary molars and correlated their non-treatment with the presence of periradicular lesion. The study was conducted on 180 cone beam computed tomography (CBCT) scans. The 180 examinations added up to 210 teeth analyzed (140 maxillary first molars and 70 maxillary second molars). The presence of non-located/treated MB2 canals and periapical lesions in the mesiobucal(MB) root was identified by observation of the axial and subsequently of sagittal and coronal slices. Among the 210 teeth evaluated, 91.4% (n=192) had MB2 canal, while 8.6% (n=18) did not have this canal. In the first molars with presence of MB2 (n=133), periapical lesion was observed in 85.0% (n=113). Among the second molars with presence of MB2 (n=59), periapical lesion was observed in 72.9% (n=43). The presence of periapical lesion in the MB root was related to the non-location/treatment of the MB2 canal and was higher when it was an independent canal.